2019
DOI: 10.3390/w11030425
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Impact on Root Water Uptake and Solute Return Flow of Different Drip Irrigation Regimes with Brackish Water

Abstract: Water scarcity and quality degradation represent real threats to economic, social, and environmental development of arid and semi-arid regions. Drip irrigation associated to Deficit Irrigation (DI) has been investigated as a water saving technique. Yet its environmental impacts on soil and groundwater need to be gone into in depth especially when using brackish irrigation water. Soil water content and salinity were monitored in a fully drip irrigated potato plot with brackish water (4.45 dSm−1) in semi-arid Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…Water resources with good quality are limited, resulting in the use of low-quality irrigation water. This can induce soil salinization, leading to crop yield reduction, decreasing the agricultural productivity, and causing general income loss [1,2]. Thus, accurate monitoring of soil salinity in time and space is of great importance for precision irrigation scheduling to save water and avoid soil degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water resources with good quality are limited, resulting in the use of low-quality irrigation water. This can induce soil salinization, leading to crop yield reduction, decreasing the agricultural productivity, and causing general income loss [1,2]. Thus, accurate monitoring of soil salinity in time and space is of great importance for precision irrigation scheduling to save water and avoid soil degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The 5TE dielectric soil sensor, which also uses the Hilhorst model for ECp estimation, was introduced in 2007 and it is much cheaper than the WET sensor [22]. Several recent studies have investigated the 5TE probe in agricultural applications [2,23,24]. The 5TE sensor has electrodes at the end of the probe that are influenced by soil density making them sensitive to any variation in soil structure and θ content [25].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this study showed the potential of the distributed sensor to provide a more accurate value of soil water content at field scale and to reduce the errors in water balance for shorter wet periods. Slama et al [26] dealt with field measurements and modeling by using Hydrus 1D to evaluate the effect of drip irrigation, irrigation regime on root uptake, root zone salinity and solute return flow to groundwater. Simulations showed that relative yield accounted for 54%, 70% and 85.5% of the potential maximal value when both water and solute stress were considered for deficit, full and farmers' irrigation, respectively.…”
Section: Model Calibration and Water Balancementioning
confidence: 99%
“…Nachshon [35] provided a review on cropland soil salinization, with examples of soil salinization processes from croplands around the world, by discussing the effects of salinity coming from different sources. Slama et al [26] also discussed the effects of different irrigation regimes on root zone salinity. Soil water content and salinity were monitored in a fully drip-irrigated potato plot with brackish water (4.45 dS/m) in semi-arid Tunisia.…”
Section: Irrigation Management and Effects On Soil Hydrological Procementioning
confidence: 99%
“…Rajmohan and Elango (2007) used HYDRUS-2D (Šimùnek et al 1999) to simulate both nitrate and chloride transport in the vadose zone and to estimate their respective solute fluxes towards groundwater. Slama et al (2019) applied HYDRUS-1D to assess the impact of different drip irrigation regimes with brackish water on soil salinization and solute return flow. 1D unsaturated models are helpful when studying solute return fluxes to groundwater, but the integration of their results to a hydrogeological model is not an easy task.…”
Section: Introductionmentioning
confidence: 99%